Sulfolane-Based Flame-Retardant Electrolyte for High-Voltage Sodium-Ion Batteries - Xuanlong He; Jie Peng; Qingyun Lin; Meng Li; Weibin Chen; Pei Liu; Tao Huang; Zhencheng Huang; Yuying Liu; Jiaojiao Deng; Shenghua Ye; Xuming Yang; et al. (Nano-Micro Letters)
Highlights NaTFSI/SUL:OTE:FEC facilitates the formation of S, N-rich, dense and robust cathode–electrolyte interphase on NaNMF cathode, which improves the cycling stability under high voltage. By utilizing NaTFSI/SUL:OTE:FEC, the Na||NaNMF batteries achieved an impressive retention of 81.15% after 400 cycles at 2 C with the cutoff voltage of 4.2 V. The study offers a reference for the utilization of sulfolane-based electrolytes in sodium-ion batteries (SIBs), while the nonflammability of the NaTFSI/SUL:OTE:FEC enhances the safety of SIBs.